Inference on winners - Isaiah Andrews; Toru Kitagawa; Adam McCloskey (Centre for Microdata Methods and Practice (cemmap), 2018)
Many questions in econometrics can be cast as inference on a parameter selected through optimization. For example, researchers may be interested in the effectiveness of the best policy found in a randomized trial, or the bestperforming investment strategy based on historical data. Such settings give rise to a winner's curse, where conventional estimates are biased and conventional confidence intervals are unreliable. This paper develops optimal confidence sets and median-unbiased estimators that are valid conditional on the parameter selected and so overcome this winner's curse. If one requires validity only on average over target parameters that might have been selected, we develop hybrid procedures that combine conditional and projection confidence sets and offer further performance gains that are attractive relative to existing alternatives.
Keywords: C12; C13; 330; Winner's Curse; Selective Inference